CORRUPTION AND ECONOMIC GROWTH IN NIGERIA: DOES DATA SUPPORT “GREASE THE WHEELS” OR “SAND THE WHEELS”? - Felix Odunayo Ajayi; Aduralere Opeyemi Oyelade; Gideon Olugbenga Olanrewaju (MESP–FEB UNS, 2024)
The study investigated the relationship between corruption and economic growth in Nigeria using data from 1996 to 2020. The research employed the Fully Modified Ordinary Least Squares (FMOLS) method and Granger causality tests. The FMOLS results indicated that both gross fixed capital formation and urbanization significantly and positively influence economic growth in Nigeria, whereas the corruption index has a negative and significant effect, aligning with the